ChemInform Abstract: Microwave‐Assisted Construction of C‐Hydroxydiketopiperazines Using Lanthanum(III) Triflate. Issue 26 (June 2015) - Wang, Qing‐Peng; Zhang, Hong‐Bo; Ning, Xin; Hang, Hang; Huang, Zhong‐Lv; Song, Hao‐Ran; Wang, Xin; Wang, Peng George
Abstract A highly efficient and convenient method for the construction of C‐hydroxydiketopiperazines is developed using Lanthanum(III) triflate as a recyclable reagent.